Pengaruh Keahlian Akuntansi, Literasi Digital dan Literasi Manusia Terhadap Kesiapan Kerja Calon Akuntan di Era Disrupsi Teknologi Digital - Melia Yulianti; Asniati Asniati; Verni Juita (Ekonomis: Journal of Economics and Business, 2021)
The development and increasing use of digital technology causes various changes. That”s made convenience and cause disruption and threaten the continuity of the existing profession like accountant. This study aims to determine that accounting skills, digital literacy and human literacy have a positive effect on the job readiness of accounting student. The population is undergraduate accounting students in the city of Padang. The research used convenience sampling technique. Determination of total samples using the slovin formula. The number of samples is 376. Data collection using by a questionnaire. The research data were analyzed with the SEM_PLS. The results of this study conclude that partially accounting skills, digital literacy and human literacy have a significant positive effect on job readiness and simultaneously this study concludes that accounting skills, digital literacy and human literacy have a significant positive effect on job readiness by 74.8%.